The implementation of fault management in distribution system using distribution automation system (DAS) in conjunction with SCADA - Ab Ghani, Mohd Ruddin; Mat Hanafiah, Mohd Ariff; Raman, Siti Hajar; Baharudin, Zikri Abadi; Wan Jusoh, Wan Nor Shela Ezwane (2012)
In general, the electric power distribution system is responsible to deliver the power from a set of distribution substation system to the customers. The operation of controlling and monitoring of electrical power activity or condition in distribution side, typically take at the distribution substation system. However the distribution substation system, often facing a problem such as required longer time to restore back the electric supply when power outage occurred. The engineer and technician manually have to locate the fault position and spend plenty of time. In addition the acknowledgement system used by Tenaga Nasional Berhad (TNB) such as Supervisory Control and Data Acquisition (SCADA) only indicate the event such fault through certain panel. Therefore, the implementation of proper fault management is highly important to be utilized such as by applying automation system in distribution system. Up to date, in Malaysia there is no automation technique being used for maintenance work in distribution system. Those problematic issues as mentioned above motivated the authors to propose the idea for implementation of Distribution Automation System (DAS) in distribution side. The major consideration in this work is to identify fault management strategy for switching circuit breaker to be implemented as new algorithm technique in SCADA. Finally, the secondary plan is to apply the new algorithm to the DAS for small scale of experimental study. It is expected the propose strategies will improve recent fault management specifically distribution system in Malaysia.